Cross sections for ionization of uracil by MeV-energy-proton impact - Itoh, A. (2013)
Absolute double differential cross sections (DDCS) have been measured for the ionization of gas-phase uracil (C4H4N2O2) by 0.5, 1.0, and 2.0 MeV proton impacts. Measurements were performed by secondary electron spectroscopy using a 45∘ parallel plate electrostatic spectrometer over an energy range of 1.0–1000 eV at emission angles from 15∘ to 165∘. Theoretical calculation of ionization cross sections has also been carried out by using the first-order Born approximation with correct boundary conditions. Single differential and total ionization cross sections deduced from DDCS revealed fairly good agreement between experimental and theoretical values at all the emission angles investigated.